Who is the sexually progressive subject? Sexual, cultural and ethnic (un)belonging among younger Iranian-Dutch. (January 2020) - Roodsaz, Rahil
Over the past two decades, issues of sexuality and gender have increasingly become instrumentalized in us/them demarcations in public debates on the position of ethnic and religious minority groups living in Western countries. In these debates, a sexually progressive West is imagined as opposed to a sexually progressive Rest, policing exclusionary and inclusionary regimes of power. This article presents a diasporic account of sexual progressiveness, focusing on the narratives of younger Iranian-Dutch. I argue that, through an imaginative state of sexual, cultural and ethnic (un)belonging, these highly educated interlocutors trouble not only the implied whiteness and universality of the sexually progressive subject, but also heteropatriarchal underpinnings of dominant nationalist and diasporic understandings of culture, home and nation.